In dubious battle: il lato oscuro del diritto nella riflessione sociale di John Steinbeck (Società e diritti, 2024)
Within the epistemological framework of law and literature, this contribution focuses its attention on the social reflection that John Steinbeck accomplishes in the “trilogy of the most vulnerable”: “In dubious battle”e (1936), “Of Mice and Men” (1937) and “The grapes of wrath” (1939), works that represent a new proletarian literature born in the early twentieth century not only to describe and interpret the world, but to help change it. In In particular, here we focus on the context described in “In dubious battle”, a novel defined by the New York Times Book Review, at the time of the publication of the work (written in 1936 and translated in Italy in 1940 by Eugenio Montale) as “the best labor and strike novel”. The effects of the economic crisis of 1929, the human and social vulnerability of the workers of the Torgas Valley, the strike as a dramatic event to defend the right to a fair wage to live a dignified life, are the background to a story in which there is an interplay between power and injustice and, with these, the dark side of law.Keywords: ETS, commercial entity, no commercial entity;